The restless anthropology of Victor Turner - Cavalcanti, Maria Laura Viveiros de Castro (GIS - Gesture, Image and Sound - Anthropology Journal, 2023)
Based on an overview on Victor Witter Turner’s theoretical background and production and a brief discussion on its reception by Brazilian anthropologists since the 1970s, this paper focuses on Turner’ first book Schism and Continuity in an African Society. Published in 1957, it resulted from research carried out by Victor and Edith Turner in the first half of the 1950s among the Ndembu, inhabitants of the northwest of present-day Zambia. The text argues that the driving creative restlessness characteristic of Turner’s work can be understood by an ethnographic reading of the concept of social drama, from which the notion of ritual emerges as a powerful narrative countercurrent. The focus on this notion allows this analysis to provide a glimpse into the author’s future conceptual developments, when the ethnography of the Ndembu dialogues with themes such as the whiteness of the whale in Herman Melville’s Moby Dick, the Nordic sagas, the pilgrimages Catholic Churches, Franciscan Orders, the Hippie Movement and Theater Performances.